Pemanfaatan Aplikasi Google Form dalam Meningkatkan Pelaksanaan Supervisi Pendidikan Pengawas Madrasah - Sri Rahmiyati (Jurnal Pendidikan Madrasah, 2019)
Utilization of the Google Form application is done as an alternative action when the supervisor of Madrasah encountered several obstacles in the field relating to the area and the number of building Madrasah. The ease of the Google Form application for daily activities is: 1) real-time distribution and tabulation; 2) Real time collaboration; 3) secure; Storing important files or school assignments is not afraid of lost or damaged or exposed to viruses. Google Form is also an easy-to-use application even for beginners, free (free to pay), usually the data results are presented in an Excel file so it is easy to use and a fairly lightweight program. Utilization of the Google Form application in assisting the oversight of the madrasah to be effective and efficient can be described as follows; 1) Facilitate the supervisors to collect data without having to meet the speakers directly, especially for speakers who are away from the location of supervision activities; 2) for the necessary data of the activity or administration report that does not require the presence of a supervisor in the field, then data retrieval through instruments created by Google Form will assist the implementation of the supervisory duties more effective and efficient madrasah. 3) Availability of features available in Google Form such as charts, tables, Excel and others, greatly supports the data needs of the madrasah supervisor.